2021
DOI: 10.3389/fmicb.2020.610269
|View full text |Cite
|
Sign up to set email alerts
|

Zebra Mussel Holobionts Fix and Recycle Nitrogen in Lagoon Sediments

Abstract: Bivalves are ubiquitous filter-feeders able to alter ecosystems functions. Their impact on nitrogen (N) cycling is commonly related to their filter-feeding activity, biodeposition, and excretion. A so far understudied impact is linked to the metabolism of the associated microbiome that together with the host constitute the mussel’s holobiont. Here we investigated how colonies of the invasive zebra mussel (Dreissena polymorpha) alter benthic N cycling in the shallow water sediment of the largest European lagoon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 97 publications
(118 reference statements)
3
21
0
Order By: Relevance
“…Filtered water was enriched with 15 N-N 2 using a modified version of the method described in Marzocchi et al (2021). Briefly, two 2-L glass bottles (Shott) were filled with 0.22µm twice-filtered in situ water and sealed with black butyl septa and screw caps, with a hollow needle in the septum to prevent the formation of air bubbles.…”
Section: Nitrogen Fixationmentioning
confidence: 99%
“…Filtered water was enriched with 15 N-N 2 using a modified version of the method described in Marzocchi et al (2021). Briefly, two 2-L glass bottles (Shott) were filled with 0.22µm twice-filtered in situ water and sealed with black butyl septa and screw caps, with a hollow needle in the septum to prevent the formation of air bubbles.…”
Section: Nitrogen Fixationmentioning
confidence: 99%
“…Considering that many Mycoplasma species are parasitic or pathogenic to humans and other animals [54,75], these findings, together with the detection of OTUs assigned to potential fish pathogens from the genera Vibrio and Acinetobacter [55][56][57][58] as the significantly most abundant in the DG microbiome from the limpets at the aquaculture cages, confirm that pathogen transfer between farmed fishes and wild limpets is possible. However, it must also be pointed out that Tenericutes, and particularly Mycoplasma, have been consistently observed as abundant, core members of several aquatic organisms' microbiome, mainly including bivalves, where they exhibit commensalism [76][77][78][79][80][81]. A possible involvement in mutually beneficial interactions with the host-likely by assisting an efficient processing of complex organic compounds, abundant at aquaculture sites-is being progressively assumed [81][82][83] and corroborates the idea of a possible role of fouling organisms in reducing the environmental impact of aquaculture [84].…”
Section: Discussionmentioning
confidence: 99%
“…However, it must also be pointed out that Tenericutes, and particularly Mycoplasma, have been consistently observed as abundant, core members of several aquatic organisms' microbiome, mainly including bivalves, where they exhibit commensalism [76][77][78][79][80][81]. A possible involvement in mutually beneficial interactions with the host-likely by assisting an efficient processing of complex organic compounds, abundant at aquaculture sites-is being progressively assumed [81][82][83] and corroborates the idea of a possible role of fouling organisms in reducing the environmental impact of aquaculture [84]. Since the OTUs assigned to the genera Mycoplasma, Vibrio, and Acinetobacter enriched in the DG microbiome from P. caerulea at the aquaculture site were not detectable in farmed fish samples and no disease was reported at the fish farming plant at the moment of sampling, we could hypothesize that relationships such as commensalism, rather than parasitism or pathogenicity, occurred between P. caerulea and OTUs belonging to these genera.…”
Section: Discussionmentioning
confidence: 99%
“…To determine rates of N 2 xation, a stock solution of 30 N 2 -enriched 0.22 µm twice-ltered water was prepared using a modi ed version of the protocol described in Klawonn et al (2015) as reported in Marzocchi et al (2021). Before starting the incubation, the stock solution was gently transferred into ve microcosms to minimize gas exchange with the atmosphere.…”
Section: Dinitrogen Xationmentioning
confidence: 99%
“…Therefore, macrofauna may stimulate an array of reactions and processes regulating benthic functioning. Macrofauna may also select and host unique microbiomes, which can contribute to biogeochemical cycling (Cardini et al 2019;Zilius et al 2020;Marzocchi et al 2021).…”
Section: Introductionmentioning
confidence: 99%